De Sokkel Onder-Uit : De Kunstbank. - Bourgois, Anne-Aymone; Universiteitsbibliotheek Leuven; De Maesschalck, Dimitri; De Rons, Katrien; Depré, Ilse; Derroitte, Bernard; Desseaux, Stefan; Gaethofs, Jurgen; Leenknegt, Pieter; Matthuysen, Vanessa; Nys, Tom; Patteeuw, Veronique; et al. (Leuven : Kunstbank vzw, 1998)
Bijl, Guillaume ; Buren, Daniel ; Deleu, Luc ; Delvoye, Wim ; François, Michel ; Kiecol, Hubert ; Mees, Guy ; Mistiaen, Carlo ; Muñoz, Juan ; Nauman, Bruce ; Pacquée, Ria ; Sherman, Cindy ; Theys, Frank & Koen ; Tuymans, Luc ; Van Caeckenbergh, Patrick ; Venlet, Richard ; Vercruysse, Jan ; Visch, Henk ; West, Franz
Nederlands
De sokkel onder/uit, Universiteitsbibliotheek, Leuven, van 29 april tot 4 juni 1998
boek